The relationship between Information Technology and Halal Logistics - Hendayani, Ratih; Fernando, Yudi; Ganesan, Yuvaraj (IEOM Society, 2018)
As a country with a majority of adherents of Islam, Indonesia is one of the countries with the largest market share of Halal products in the world. The emergence of Halal-labeled food and beverage products businesses is growing even imported products entering Indonesia are beginning to register their certification to MUI, indicating that the level of consumer awareness of Halal products in Indonesia has increased. The case of Samyang noodles in Indonesia has recently become one proof that imported products must also have Halal certification. Social media as one of the most widely used technologies today, is rapidly influencing consumers that the products that are logistically distributed from Korea are Haram and directly lower the benefits of this product which was originally the most popular and viral in social media. This is to prove that the role of technology, the logistics process will affect the profitability of a company for its products, so that through this research will be proven empirically. This study is a descriptive quantitative research with questionnaires distributed to 100 respondents who have appropriate criteria as the object of this research is the producers of halal food. Data processing using descriptive data analysis technique and simple linier regression analysis technique using SPSS 23 software. The results are the Information Technology supports have positive and significant relationship with Halal Logistics. The model in this study can use to investigate the relationship of Halal Logistics and Information Technology in Halal cosmetics, Halal medicine, and others, for further study.